2022
DOI: 10.1111/jfpe.14163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasound processing on the quality of guava juice

Abstract: Ultrasound has been found to be a non-thermal method for inactivating microorganisms pertinent to fruit juices. The current research was planned with the goal of investigating the influence of sonication on the quality of guava juice when treated at a constant 40 kHz frequency, 200 W radiating power for different processing times of 2, 6, and 10 min in ultrasonic bath. After ultrasound treatment, the values of pH and titratable acidity varied non-significantly (p > 0.05), while 6 min of sonication showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…The results of the present research showed that titratable acidity is optimally maintained by increasing the temperature and US time, which is likely due to the decrease in ethylene production and inhibition of respiration as a result of US treatment. Our results were in line with the findings of other researchers on guava (Kalsi et al, 2022), strawberry (Maryam et al, 2021), and pomegranate fruit (Moradinezhad et al, 2023).…”
Section: Titratable Aciditysupporting
confidence: 94%
“…The results of the present research showed that titratable acidity is optimally maintained by increasing the temperature and US time, which is likely due to the decrease in ethylene production and inhibition of respiration as a result of US treatment. Our results were in line with the findings of other researchers on guava (Kalsi et al, 2022), strawberry (Maryam et al, 2021), and pomegranate fruit (Moradinezhad et al, 2023).…”
Section: Titratable Aciditysupporting
confidence: 94%
“…Te value L * is the measure of lightness which vary from zero for black to 100 for perfect white, value a * measures redness when positive/ greenness when negative, and value b * measures yellowness when positive/blueness when negative. Tese values (L * ,a * , and b * ) were converted into chroma [28] and hue angle [29] using following equations ( 7) and ( 8):…”
Section: Color Characteristicsmentioning
confidence: 99%
“…A portable colorimeter (Konica Minolta Sensing Inc, Japan) was used to determine the colour of the samples 20 . The colour is defined by the tristimulus values L, a, and b.…”
Section: Methodsmentioning
confidence: 99%